2021
DOI: 10.3389/fped.2021.668546
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Molecular Genetics of Timothy Syndrome

Abstract: Timothy Syndrome (TS) (OMIM #601005) is a rare autosomal dominant syndrome caused by variants in CACNA1C, which encodes the α1C subunit of the voltage-gated calcium channel Cav1.2. TS is classically caused by only a few different genetic changes and characterized by prolonged QT interval, syndactyly, and neurodevelopmental delay; however, the number of identified TS-causing variants is growing, and the resulting symptom profiles are incredibly complex and variable. Here, we aim to review the genetic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 64 publications
1
36
0
2
Order By: Relevance
“…Our experiments and modeling of the TiS G406R mutation (Bauer et al, 2021;Dick et al, 2016;Splawski et al, 2004Splawski et al, , 2005 suggest that CaV1.2 LTCCs act not as sensors of activity changes, but as effectors recruited for homeostatic adaptations. LTCCs are known to interact with multiple postsynaptic elements such as AKAP67/150 (Dittmer et al, 2014;Oliveria et al, 2007), PKA (Diering et al, 2014;, CaN (Sanderson et al, 2012;Xu et al, 2010) and CaMKII (Li et al, 2016;Oliveria et al, 2007) and play central roles in signaling synaptic activity to the nucleus (Deisseroth et al, 1996;Greenberg et al, 1986;Li et al, 2016;Ma et al, 2014;Mandelberg, 2020;Morgan and Curran, 1986;Murphy et al, 2014;Wheeler et al, 2008).…”
Section: Cav12 Channels Act As Homeostatic Effectors: Insights From A...mentioning
confidence: 86%
See 1 more Smart Citation
“…Our experiments and modeling of the TiS G406R mutation (Bauer et al, 2021;Dick et al, 2016;Splawski et al, 2004Splawski et al, , 2005 suggest that CaV1.2 LTCCs act not as sensors of activity changes, but as effectors recruited for homeostatic adaptations. LTCCs are known to interact with multiple postsynaptic elements such as AKAP67/150 (Dittmer et al, 2014;Oliveria et al, 2007), PKA (Diering et al, 2014;, CaN (Sanderson et al, 2012;Xu et al, 2010) and CaMKII (Li et al, 2016;Oliveria et al, 2007) and play central roles in signaling synaptic activity to the nucleus (Deisseroth et al, 1996;Greenberg et al, 1986;Li et al, 2016;Ma et al, 2014;Mandelberg, 2020;Morgan and Curran, 1986;Murphy et al, 2014;Wheeler et al, 2008).…”
Section: Cav12 Channels Act As Homeostatic Effectors: Insights From A...mentioning
confidence: 86%
“…These hitherto-overlooked dynamics require an ordered sequence of CaN deactivation (Kim and Ziff, 2014) and CaMKII recruitment and activation (Thiagarajan et al, 2002). We also found that LTCCs tune these dynamics, by studying responses in neurons harboring a Ca v 1.2 mutation associated with Timothy Syndrome, a rare but highly penetrant form of autism (Bauer et al, 2021; Dick et al, 2016; Splawski et al, 2004). Building on these experimental observations, we propose a quantitative model of synaptic homeostasis that incorporates dynamic interactions between positive and negative feedback signaling.…”
Section: Introductionmentioning
confidence: 96%
“…Patients with TS are treated clinically with antiarrhythmics of the B-adrenergic blocker type, with propranolol and nadolol being more effective [11,12] Although studies have shown a reduction in adverse cardiac events in STQL type 1, these antiarrhythmics are insu cient to prevent lethal arrhythmias in patients with TS [11,12,13]. Therefore, new therapies for ST are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] This is now referred to as the CACNA1C-related disorder (CRD) spectrum that encompasses a range of clinical features caused by pathogenic variants predicted to both increase and decrease channel function. 31,32 A better understanding of the epidemiology, clinical spectrum, and biological phenotype of highly penetrant monogenic disease models such as CRD would help unravel how calcium signaling affects neuropsychiatric disorders more broadly and how modulation of calcium pathways could be leveraged for therapeutic purposes. A major gap in the field is that neuropsychiatric symptoms are not well characterized in the CRD literature beyond the early TS1 cohort and very recent neurologic-only CRD cohort.…”
Section: Introductionmentioning
confidence: 99%
“…27–30 This is now referred to as the CACNA1C -related disorder (CRD) spectrum that encom-passes a range of clinical features caused by pathogenic variants predicted to both increase and decrease channel func tion. 31,32…”
Section: Introductionmentioning
confidence: 99%